Relaxation and strain among emergency medical service personnel and emergency control center dispatchers during the first two waves of the SARS-CoV-2 pandemic - Heiko Schumann; Irina Böckelmann; Beatrice Thielmann (Nofer Institute of Occupational Medicine, 2023)
Background Workloads of emergency medical service personnel (EMP) and emergency control center dispatchers (CCDs) were manifold. The SARS-CoV-2 pandemic presented new challenges for the prehospital emergency medical service. The purpose of this study was to compare the status of stress/strain and recovery of Recovery-Stress Questionnaire among EMP and CCDs in Germany during the first 2 waves of the SARS-CoV-2 pandemic both between occupational groups and over time. Material and Methods A total of 2426 emergency medical service personnel and control center dispatchers were questioned with the Recovery-Stress Questionnaire based on Kallus. The results from the first 2 waves of the pandemic (June-August 2020 and January-February 2021) were compared. Results During the first and second wave of SARS-CoV-2 pandemic, the subjectively perceived stress of emergency medical service personnel and control center dispatchers increased, but recovery decreased. The CCDs showed more unfavorable values compared to EMP. Conclusions Health promotion interventions are necessary to counteract possible career changes or mental or other diseases due to insufficient management. Med Pr Work Health Saf. 2023;74(5):353-62.